Analisis Nilai Pendidikan Karakter Michael Josephson Tokoh Karang dalam Novel Aku Tak Membenci Hujan Karya Sri Puji Hartini - Mulia Putri Khasanah; Rani Jayanti; Asih Andriyati Mardliyah (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the values ​​of character education based on Michael Josephson's theory in the character Karang in the novel Aku Tak Membenci Hujan by Sri Puji Hartini. The approach used is a qualitative descriptive method, with data analysis techniques in the form of identifying quotations that describe the six pillars of character according to Josephson: trust, respect, responsibility, justice, caring, and citizenship. The results of the analysis show that the character Karang embodies five of the six main values ​​of the character, which are seen through his behavior, attitude, and social relations. These values ​​not only strengthen the dimensions of Karang's character, but also become an important reflection for readers about the meaning of personality, resilience, and interpersonal relationships.